Histological Evidences of Autograft of Dentin/Cementum Granules into Unhealed Socket at 5 Months after Tooth Extraction for Implant Placement - Masaru Murata; Md Arafat Kabir; Yukito Hirose; Morio Ochi; Naoto Okubo; Toshiyuki Akazawa; Haruhiko Kashiwazaki (Journal of Functional Biomaterials, 2022)
The aim of this clinical case study was to observe biopsy tissues at 5 months after an autograft of a partially demineralized dentin/cementum matrix (pDDM) into a tooth-extracted socket exhibiting healing failure. A 66-year-old female presented with healing failure in the cavity for 2 months after the extraction (#36). Initial X-ray photos showed a clear remainder of lamina dura (#36), a residual root (#37), and a horizontal impaction (#38). The vital tooth (#38) was selected for pDDM. The third molar crushed by electric mill was decalcified in 1.0 L of 2.0% HNO3 for 20 min and rinsed in cold distilled water. The pDDM granules (size: 0.5–2.0 mm) were grafted immediately into the treated socket. X-ray views just after pDDM graft showed radio-opaque granules. At 5 months after pDDM graft, the surface of regenerated bone was harmonized with the mandibular line, and bone-like radio-opacity was found in the graft region. The biopsy tissue (diameter: 3.0 mm) at 5 months after pDDM graft showed that mature bone was interconnected with the remaining pDDM. The novel histological evidence highlighted that newly formed bone was connected directly with both dentin-area and cementum-area matrix of pDDM. We concluded that pDDM contributed to the regeneration of bone in the unhealed socket, and this regeneration prepared the socket for implant placement. Autogenous pDDM could be immediately recycled as an innovative biomaterial for local bone regeneration.